GROSS INCOME MULTIPLIER AS A FAIRNESS INDICATOR OF TRANSACTION VALUE ON TRANSFER OF RIGHTS ON LAND AND BUILDING IN SOUTH TANGERANG - Hendrastuti, Nur (PLANNING MALAYSIA, 2021)
As the government of Indonesia targets income tax to contribute 50,1% of the overall tax revenue target in Indonesia, the Directorate General of Taxes (DGT) is compelled to maximize the excavation of tax potential. Among others, excavation of income tax potential may apply for income tax upon the transfer of rights on land and/or building. For this final income tax, tax extraction is performed by evaluating the transfer transaction value stated in the Land Deed Officer Monthly Report which should be based on the value received or obtained by the seller based on market price. Unfortunately, there is no means to ensure that the value stated by taxpayer is the actual transaction value. Also, since data on property in Indonesia is not publicly available, the real value of the transfer remains elusive. Therefore, Tax Office requires a method or technique to determine whether the stated value is a reasonable and compliant one. This research aims to examine the feasibility of Gross Income Multiplier to determine the fairness indication of transaction value stated by the taxpayer in the transfer of rights on land and/or building. By understanding the fairness of the stated value as reported in the Land Deed Officer monthly report, DGT is expected to accurately determine the fair transaction value.